2022
DOI: 10.1111/cns.13999
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen improves depression‐like behaviors in chronic stress model mice by remodeling gut microbiota and regulating host metabolism

Abstract: Aims: There is growing evidence that the gut microbiota plays a significant part in the pathophysiology of chronic stress. The dysbiosis of the gut microbiota closely relates to dysregulation of microbiota-host cometabolism. Composition changes in the gut microbiota related to perturbations in metabolic profiles are vital risk factors for disease development. Hyperbaric oxygen therapy is commonly applied as an alternative or primary therapy for various diseases. Therefore, a metabolic and gut bacteria perspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Environmental and social factors may also influence risk for stroke, with recognition of the impact of commensal microorganisms on health and disease. 59,60 Emerging gut-brain-microbiome research using murine models, humanized mouse models, and human clinical trials 61,62 has shown that microbiome-related metabolic changes can be induced by stress, 63 exercise, 64 and even changes in the circadian rhythm. These alterations in metabolite composition have been shown across different brain regions, peripheral organs, and in circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental and social factors may also influence risk for stroke, with recognition of the impact of commensal microorganisms on health and disease. 59,60 Emerging gut-brain-microbiome research using murine models, humanized mouse models, and human clinical trials 61,62 has shown that microbiome-related metabolic changes can be induced by stress, 63 exercise, 64 and even changes in the circadian rhythm. These alterations in metabolite composition have been shown across different brain regions, peripheral organs, and in circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies included in this systematic review reported a significant increase in the following factors: the maximal oxygen uptake capacity and the relief of depressive symptoms in subjects treated with HIIT ( Choi et al., 2018 ; Chrysohoou et al., 2015 ; Dall et al., 2015 ; Flemmen et al., 2014 ; Freyssin et al., 2012 ; Plag et al., 2020 ). This observation may be rationalized as follows: increased maximal oxygen uptake capacity enhances cardiorespiratory fitness, which in turn promotes cerebrovascular function, neuronal growth and connectivity, and gut flora metabolism ( Bang-Kittilsen et al., 2022 ; Chaddock-Heyman et al., 2013 ; Zhang et al., 2022 ). Additionally, higher maximal oxygen uptake was associated with greater brain volume and protein integrity ( Chaddock-Heyman et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported a potential target for the treatment of depression, hypoxia inducible factor-1 (HIF-1), by mediating mitochondrial metabolism in response to the phenomenon of oxidative stress occasioned by insufficient oxygen levels in tissues ( Kang et al., 2021 ). Intermittent hypoxic acclimatization training with hyperbaric oxygen therapy could increase HIF-1 expression and alleviate depressive symptoms in subjects ( Kang et al., 2021 ; Zhang et al., 2022 ). It is noteworthy that HT treatment also increased HIF-1 expression in the body, which may also contribute to the alleviation of depressive symptoms via HIIT ( Holloway et al., 2015 ; Tryfonos et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, chronic unpredictable mild stress is currently considered the most widely used method for modeling chronic stress in animals. It has been employed to investigate the effects of chronic stress on various conditions, including colonic inflammation, gastric precancerous lesions, depression, and other systemic disease [36].…”
Section: Discussionmentioning
confidence: 99%